Uji Model Keberlangsungan dan Status Keberhasilan Kelompok Usaha Bersama Sebagai Bahan Evaluasi Program - Risnandar Risnandar (Universitas Merdeka Madiun, 2022)
This study's aim is to evaluate the development of the KUBE Stimulant Assistance Program, both technically and non-technically. This background study is to examine the structural model built by constructing variables that hypothetically affect the sustainability of a KUBE unit. In addition, when we reviewed the successful aspects of the KUBE, which aspect is the most dominant factor. This sample took purposively from 186 KUBE (Fiscal Year 2016-2017) in 13 provinces and 16 cities. The results show us that from the aspect of program assistance, the quality of the human resources of the assistance is quite capable in terms of the age range, length of assistance, and education, in the other hand, from the Beneficiary Families (KPM) aspect, their age are still in productive age and there is a tendency for the type of KPM's business, these results can be important information for policymakers to make a policy that is relevant to the program in the future, especially in budgeting. Furthermore, for the structural model test, in the first model (Sustainability Model) the construct variables yet cannot explain the model significantly, but what needs to be underlined is that the partnership and social support variables become valid construct variables, so that it can be used in the next model improvement. Meanwhile, in the second model (Success rate Model), the construct variables indeed explain the model significantly, the model test results that the institutional aspect becomes the dominant factor in explaining the success rate of KUBE.